Adsorption of Hydrogen Sulfide on Reduced Graphene Oxide-Wrapped Titanium Dioxide Nanofibers - Kanchit Kamlangkla; Aphichard Phongphala; Udomdej Pakdee (Adsorption Science & Technology)
This work presents a fabrication of room-temperature gas sensor for hydrogen sulfide (H2S) adsorption. Pristine titanium dioxide (TiO2) nanofibers, reduced graphene oxide (rGO) sheets, and reduced graphene oxide-wrapped titanium dioxide (rGO-wrapped TiO2) nanofibers were presented in the form of integrated suspension used for a gas-sensing layer. The TiO2 nanofibers were firstly synthesized by using an electrospinning method with a polyvinylpyrrolidone (PVP) polymer. The rGO sheets were then wrapped around TiO2 nanofibers by a hydrothermal method. Scanning electron microscope, transmission electron microscope, X-ray diffractometer, and Raman spectrometer confirmed the presence of rGO sheets onto the surface of TiO2 nanofibers. Ultraviolet-visible spectrophotometer was also considered and displayed to calculate the band gap of TiO2 and rGO-wrapped TiO2 nanofibers. After preparing the gas-sensing suspensions, they were dropped onto the polyethylene terephthalate substrates with silver-interdigitated electrodes. The gas-sensing properties of sensors were evaluated for H2S adsorption at room temperature. Based on the results, the rGO-wrapped TiO2 nanofiber gas sensor exhibited higher H2S sensitivity and selectivity than pristine TiO2 nanofiber and pure rGO gas sensors. The H2S-sensing mechanism of rGO-wrapped TiO2 nanofiber gas sensor was discussed based on a formation of p-n heterojunctions between p-type rGO sheets and n-type TiO2 nanofibers. Furthermore, a direct charge-transfer process by physisorption was also highlighted as a second H2S-sensing mechanism.